2020
DOI: 10.2340/00015555-3516
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Atopic Dermatitis

Abstract: Despite advances in atopic dermatitis (AD) treatments, research into AD prevention has been slow. Systematic reviews of prevention strategies promoting exclusive and prolonged breastfeeding, or interventions that reduce ingested or airborne allergens during pregnancy and after birth have generally not shown convincing benefit. Maternal/infant supplements such as Vitamin D have also not shown any benefit with the possible exception of omega-3 fatty acids. Systematic reviews suggest that probiotics could reduce … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 65 publications
0
20
0
5
Order By: Relevance
“…The authors also studied the hypothesis that probiotics could reduce the incidence of AD by about 20%. Improving the skin barrier from birth to prevent AD and food allergy were also one of the prevention options addressed throughout the study [12].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors also studied the hypothesis that probiotics could reduce the incidence of AD by about 20%. Improving the skin barrier from birth to prevent AD and food allergy were also one of the prevention options addressed throughout the study [12].…”
Section: Resultsmentioning
confidence: 99%
“…Primary prevention refers to intervention before health effects occur. Secondary prevention involves detecting the disease at an early stage in order to prevent its worsening and tertiary prevention is the reduction of symptoms or improvement in the quality of life of those with an already established disease [12].…”
Section:  Biological Therapymentioning
confidence: 99%
“…Vitamin D is thought to have effects on skin barrier function as well as immune system function. 73,74 Atopic dermatitis seems to be correlated with low vitamin D; 73,[75][76][77] however, the causation of this relationship is disputed between 2 leading theories: (1) low sun exposure leads to decreased vitamin D production which impacts AD-related cytokine activity, 78 (2) the chronic inflammation caused by AD produces a low vitamin D state. 79 A systematic review of vitamin D supplementation for primary prevention 74 of atopic dermatitis found little evidence that antepartum or infant supplementation prevented development of atopic dermatitis.…”
Section: Vitamin D and Chronic Painmentioning
confidence: 99%
“…Большинство периваскулярных Т-лимфоцитов выявляется в активированном состоянии, о чем свидетельствует высокая экспрессия HLA-DR и рецепторов к IL-2, что, в свою очередь, косвенно свидетельствует о постоянной готовности иммунных клеток кожи к специфическому ответу на антиген. Т-лимфоциты несут на своей поверхности кожный лимфоцитарный антиген (CLA), наличие которого обеспечивает быстрое перемещение этих клеток в кожу после экспозиции с чужеродным антигеном [17].…”
Section: основная частьunclassified